IEEE International Conference on Image Processing 2005 2005
DOI: 10.1109/icip.2005.1530213
|View full text |Cite
|
Sign up to set email alerts
|

Fast 3D face recognition based on normal map

Abstract: This paper presents a 3D face recognition method aimed to biometric applications. The proposed method compares any two faces represented as 3D polygonal surfaces through their corresponding normal map, a bidimensional array which stores local curvature (mesh normals) as the pixel's RGB components of a color image. The recognition approach, based on the computation of a difference map resulting from the comparison of normal maps, is simple yet fast and accurate. A weighting mask, automatically generated for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, the surface normal, which determines (at each point) the orientation of a facial surface, has not been well explored for 3D face representation 1 . To the best of our knowledge, Abate et al [27,28,29,30] introduced normal maps to describe facial surfaces. But this direct use of normal information in the holistic way did not achieve satisfying results.…”
Section: Motivations and Our Solutionsmentioning
confidence: 99%
“…However, the surface normal, which determines (at each point) the orientation of a facial surface, has not been well explored for 3D face representation 1 . To the best of our knowledge, Abate et al [27,28,29,30] introduced normal maps to describe facial surfaces. But this direct use of normal information in the holistic way did not achieve satisfying results.…”
Section: Motivations and Our Solutionsmentioning
confidence: 99%
“…Mohammadzade and Hatzinakos [37] showed that the surface normal vectors of the 3D faces are more useful for recognition purposes, thus, they contain more discriminative information at the sampled points than the coordinates of those points. Abate et al [38] proposed a normal map‐based 3D face recognition method for biometric applications. The normal map is a bi‐dimensional array which represents local curvature of a 3D polygonal mesh in terms of RGB colour data.…”
Section: Gradient‐based Feature Extractionmentioning
confidence: 99%
“…Abate et al developed a simple, fast and accurate recognition method in which a difference map is calculated from the comparison of normal maps of two faces [33]. The surface normals and curvature are represented by a polygonal mesh and then projected as an RGB image which is a 2D representation of a 3D mesh.…”
Section: Related Workmentioning
confidence: 99%